Approaches to monumental landscapes of the ancient Maya - Houk, Brett A. (Brett Alan), 1967-; Arroyo, Bárbara; Powis, Terry G.; Chase, Arlen F. (Arlen Frank), 1953-; Chase, Diane Z. (Maya studies., 2020)
This volume brings together a wide spectrum of new approaches to ancient Maya studies in an innovative exploration of how the Preclassic and Classic Maya shaped their world. Moving beyond the towering temples and palaces typically associated with the Maya civilization, contributors present unconventional examples of monumental Maya landscapes.